Camel milk ameliorates hyperglycaemia and oxidative damage in type-1 diabetic experimental rats. Issue 3 (7th September 2016) - Meena, Sunita; Rajput, Yudhishthir S; Pandey, Amit K; Sharma, Rajan; Singh, Raghvendar
Abstract : This study was designed to assess anti-diabetic potential of goat, camel, cow and buffalo milk in streptozotocin (STZ) induced type 1 diabetic albino wistar rats. A total of 48 rats were taken for the study where one group was kept as non-diabetic control group (8 rats) while others (40 rats) were made diabetic by STZ (50 mg/kg of body weight) injection. Among diabetic rats, a control group (8 rats) was kept and referred as diabetic control whereas other four groups (8 rats each) of diabetic rats were fed on 50 ml of goat or camel or cow or buffalo milk for 4 weeks. All the rats (non-diabetic and diabetic) were maintained on standard diet for four weeks. STZ administration resulted in enhancement of glucose, total cholesterol, triglyceride, low density lipoprotein, HbA1c and reduction in high density lipoprotein in plasma and lowering of antioxidative enzymes (catalase, glutathione peroxidase and superoxide dismutase) activities in pancreas, kidney, liver and RBCs, coupled with enhanced levels of TBARS and protein carbonyls in pancreas, kidney, liver and plasma. OGTT carried out at the end of 4 week milk feeding indicated that all milks helped in early maintenance of glucose level. All milks reduced atherogenic index. In camel milk fed diabetic group, insulin concentration enhanced to level noted for non-diabetic control while goat, cow and buffalo milk failed to restore insulin level. HbA1c level was also restored only in camel milk fed diabetic group. The level of antioxidative enzymes (catalase, GPx and SOD) in pancreas enhanced in all milk fed groups. Camel milk and to a reasonable extent goat milk reduced formation of TBARS and PCs in tissues and blood. It can be concluded that camel milk ameliorates hyperglycaemia and oxidative damage in type-1 diabetic experimental rats. Further, only camel milk completely ameliorated oxidative damage in pancreas and normalised insulin level.